1996
DOI: 10.1136/vr.138.19.468
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sarcoptic mite infestation and mite hypersensitivity in pigs with injectable doramectin

Abstract: Thirty-two pigs were infested experimentally with Sarcoptes scabiei var suis and allocated randomly to a medicated group (injected intramuscularly with 300 micrograms doramectin/kg) or an unmedicated group (injected intramuscularly with 1 ml saline/33 kg). They were observed daily for 15 minutes for signs of pruritus, and the ear lesions were assessed and skin scrapings examined for mites on days 7, 14, 21 and 28 after treatment. In the 16 pigs treated with doramectin the ear lesions resolved completely within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Efficacy of a single dose of injectable doramectin in the treatment of S. scabiei infestation in cattle (Logan et al . 1993) and pigs (Cargill et al . 1996) has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of a single dose of injectable doramectin in the treatment of S. scabiei infestation in cattle (Logan et al . 1993) and pigs (Cargill et al . 1996) has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration of dead mange mites in ear scrapings following day 0 was not surprising, even though mites were absent in experimental trials within 28 days following efficacious treatment [6,7]. The severity and chronic nature of the mange infestation in these 2 herds, as well as the total number of animals examined by scrapings following treatment (452 in Herd A and 918 in Herd B ) may provide the answer.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, the results from an experimental trial [6] and results reported in a field trial [17], the single injection strategy is effective when using doramectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seit der Einführung der breit wirksamen Antiparasitika wie Ivermectin (6,11,15,22,23) oder Doramectin (3,6,20) ist es heute möglich, die Räude in infizierten Betrieben als Alternative zur Totalsanierung mit dem SPF-Verfahren medikamentös zu tilgen (16,27). Sowohl die perorale als auch die parenterale Applikation unter strenger Einhaltung des vorgeschriebenen Behandlungsschemas, mit oder ohne zusätzliche lokale Waschbehandlung der Tiere und deren Umgebung, erbrachte in unseren Untersuchungen absolute Sanierungserfolge.…”
Section: Diskussionunclassified